2017
DOI: 10.1097/icl.0000000000000247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lens Care Systems on Silicone Hydrogel Contact Lens Hydrophobicity

Abstract: This study reveals the existence of interactions between CL material and lens solutions that can play an important role in CL surface wettability. The major changes were obtained in lenses with higher baseline CA, which showed significant changes with each of the solutions. These differences can be positive, because in almost all of the combinations, the lenses became more wettable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
(42 reference statements)
0
16
0
Order By: Relevance
“…It should be noticed that both in our control experiments (data not shown) and in publications by independent teams TE and AOD type of materials were found to display advancing contact angles ≥47° even in absence of desiccation stress and with all the wetting agents being present (i.e., with the CLs freshly removed from blisters and without exposure to air) [7,21,22,28,29]. Considering that it has been claimed [30] that the internal wetting agents infused in the core of senofilcon A and narafilcon A are not blink released (i.e., significantly resisting a depletion by the aqueous tear turnover) it is further indication on the importance of true surface coatings/treatments for the low water CA of CL.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…It should be noticed that both in our control experiments (data not shown) and in publications by independent teams TE and AOD type of materials were found to display advancing contact angles ≥47° even in absence of desiccation stress and with all the wetting agents being present (i.e., with the CLs freshly removed from blisters and without exposure to air) [7,21,22,28,29]. Considering that it has been claimed [30] that the internal wetting agents infused in the core of senofilcon A and narafilcon A are not blink released (i.e., significantly resisting a depletion by the aqueous tear turnover) it is further indication on the importance of true surface coatings/treatments for the low water CA of CL.…”
Section: Discussionmentioning
confidence: 64%
“…of the CL performance [1,14,28]. The data on the impact of internal wetting agents on the contact angles of worn SiHy CLs are also inconclusive [7,8] and although it was found that the presence of PVP (wetting agent) does not significantly improve the clinical performance of SiHy [31], the small sample size (40 patients per CL sample) limited the statistical power of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcon proposed to exploit this phenomenon in OPTI‐FREE Puremoist to enhance the wettability of silicone hydrogel contact lens surfaces (Campbell et al, ). Indeed, Lira and Silva evaluated the change in the wettability of five lens models after incubation with four MPSs and reported lower water contact angles on four of the five lenses tested after incubation with OPTI‐FREE Puremoist relative to their respective angles measured just out of the packing solution,(Lira & Silva, ) which was also true with ReNu MultiPlus MPS (Bausch and Lomb) containing Tetronic 1107 surfactant.…”
Section: Discussionmentioning
confidence: 92%
“…Tear film dysfunction causes pain and enhanced immune activity, which may interfere with vision [18]. Some studies have shown that the coefficient of friction (COF) of silicone hydrogels may be changed due to long-term reaction with the tear film components, indicating that long-lasting moist lens is favourable for maintaining a low COF in a long time [19], and some research studies related to the design of novel highly weTable contact lens materials have been done already [20][21][22]. Blinking and eye rotation are the most important physiological processes for lens and lens friction, which can lead to various corneal infections, corneal ulcers, decreased vision, and other symptoms [23].…”
Section: Introductionmentioning
confidence: 99%